1995
DOI: 10.1111/j.1432-1033.1995.0517k.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Human Papillomavirus Type 16 El and E2 Proteins is Blocked by An Antibody to the N‐Terminal Region of E2

Abstract: El could be blocked by a monoclonal antibody that bound E2 in the region of amino acids 18-41 of E2 whereas a monoclonal antibody reactive with a nearby part of the molecule (amino acids 2-17) only partially blocked this interaction. These results suggest that a region in the N-terminus of E2 around amino acids 18-41 is a site of interaction with the E l protein.Keywords. Papillomavirus; HPV16; E l ; E2; protein interactions.The papillomaviruses are a group of over 70 types of doublestranded DNA viruses that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
5
27
0
Order By: Relevance
“…SDS ± PAGE and Western blots were performed on Protan nitro-cellulose (Schleicher and Schuell) as described by Harlow and Lane (1988). E2 was detected with the mouse monoclonal antibody TVG261 (Hibma et al, 1995). Secondary antibodies were HRP-conjugated antimouse or anti-rabbit and detected with ECL.…”
Section: Protein Extract Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…SDS ± PAGE and Western blots were performed on Protan nitro-cellulose (Schleicher and Schuell) as described by Harlow and Lane (1988). E2 was detected with the mouse monoclonal antibody TVG261 (Hibma et al, 1995). Secondary antibodies were HRP-conjugated antimouse or anti-rabbit and detected with ECL.…”
Section: Protein Extract Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…Protein concentrations were determined using the Bio-Rad protein assay and equal amounts were run on PAGE and transferred to a nitrocellulose membrane. HPV-16 E2 protein was detected using a pool of the anti-E2 monoclonal antibodies TVG 261 and TVG 271 (Hibma et al, 1995), followed by incubation with rabbit anti-mouse biotin conjugate (DAKO) and avidin peroxidase HPV DNA replication HPV DNA replication conjugate (DAKO). Blots were developed using the Amersham ECL system according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The full-length E2 protein is able to bind to the E1 protein through its N terminus and recent studies have identified two widely separate regions of the E2 protein which are essential for this binding Piccini et al, 1995 ;Hibma et al, 1995). To date, one detailed analysis of regions of the HPV-16 E2 protein important for viral DNA replication has been reported (Sakai et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…E. eoli TB1 cells bearing these recombinant vectors, pGEXElwt and pGEXE1Pro, were cultured in 1 M-sorbitol + 2.5 mM-betaine in LB medium and induced with 0.3 mM-IPTG when the optical densities of the cultures at 600 nm were 0.8-1-2, to express GSTElwt and GSTE1Pro respectively. The inductions were carried out at room temperature for 16 h. Bacteria were harvested and the fusion proteins purified according to the method described by Hibma et al (1995). Essentially, the bacterial pellets were resuspended in 20 ml of lysis buffer (50 mM-Tris-HC1, 10 mM-2-mercaptoethanol, 100 mM-NaC1, 1 mM-EDTA, 20 mM-MgC12, 1 mM-azide and 10% glycerol), freeze-thawed and sonicated for three rounds of 30 s each.…”
Section: Methodsmentioning
confidence: 99%
“…Interaction with E2-binding assays were performed as described previously (Hibma et al, 1995). Essentially, GST, GSTElwt and GSTE1Pro immobilized on glutathione Sepharose resin were incubated with bacterially expressed and purified native HPV-16 E2 protein (gift from M. Hibma, University of Otago, New Zealand) in binding buffer (20 mN-Tris-HC1 pH 8, 70 mM-KC1, 2mM-MgC12, 20 gM-zinc acetate, 0.2 mM-DTT, 6% glycerol, 0.1% Tween 20, 2% BSA, 2 lag calf thymus DNA) for 1 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%